Exosomes, an Unmasked Culprit in Neurodegenerative Diseases - Soria, Federico N.; Pampliega, Olatz; Bourdenx, Mathieu; Meissner, Wassilios G.; Bezard, Erwan; Dehay, Benjamin (Frontiers in Neuroscience, 2017)
Exosomes are extracellular nanovesicles (30-100 nm) generated from endosomal membranes and known to be released by all cell lineages of the Central Nervous System (CNS). They constitute important vesicles for the secretion and transport of multilevel information, including signaling, toxic and regulatory molecules. Initially thought to have a function merely in waste disposal, the involvement of exosomes in neuronal development, maintenance and regeneration through its paracrine and endocrine signaling functions has drawn particular attention in recent years. These vesicles, being involved in the clearance and cell-to-cell spreading of toxic molecules, have been naturally implicated in aging, and in several neurodegenerative diseases associated with pathological conversion of proteins, as well as in the transport of other disease-associated molecules, such as nucleic acids or pro-inflammatory cytokines. Our understanding of such unique form of communication may provide not only answers about (patho)physiological processes in the brain, but can also offer means to exploit these vesicles as vehicles for the delivery of biologically relevant molecules or as tools to monitor brain diseases in a non-invasive way. A promising field in expansion, the study of exosomes and related extracellular vesicles has just commenced to unveil their potential as therapeutic tools for brain disorders as well as biomarkers of disease state.